Discharge Profile and Its Correlation with Estimated Parametric Sensitivity and Electrical Contact Resistance Losses in Li-Ion Battery. Issue 11 (9th November 2021) - Selvi, G. Thamarai; Jha, Shailendra K.
Abstract : The electrochemistry-based models contain a large number of parameters and their sensitivity estimation is essential to obtain an accurate Li-ion battery model. The mitigation of interfacial contact resistance and associated ohmic loss and/or power loss in the real time evaluation of a battery performance is an important issue in the energy management. A compact analytical model for cell voltage and the discharge profile of Li-ion battery has been developed to analyze the impact of parametric sensitivity and interfacial contact resistance loss. The cell voltage of the battery depends on the polarization effect due to the anodic and/or cathodic overpotential and the contact resistance of the electrode/current collector interface. The impact of parametric sensitivity and with/without contact resistance on cell voltage analysis for a discharge process have been investigated and verified with the available experimental literature data.